Digital Construction Community of Gojek Women’s Drivers in DKI Jakarta - Badruddin, Syamsiah; Barakat, Hadi Farras (Indonesian Journal of Digital Society is a scientific journal, 2020)
This study aims to determine the community construction of female Gojek drivers and the problems faced by Gojek female drivers. The object of the study was conducted in DKI Jakarta. Researchers used qualitative research methods with data collection techniques namely observation, interviews, documentation, and literature review. The results showed that the community construction of female Gojek drivers is also an externalization process that cannot be separated from the internalization process. The giving of different symbols is then understood by individuals as a process of objectivation. From the formations they have made through the process of objectivation, there will be different understandings in themselves about the female Gojek drivers. Generally the attitudes and behaviors of the community towards female Gojek drivers also have different ways. The community's understanding of the female Gojek drivers varies. Depending on how the situation or condition they face by users such as informants that researchers meet. Keywords : Digital Construction Community, Gojek Women’s Driver.